The Effect of Service Quality and Passenger Satisfaction on Bus Passenger Loyalty Tawang Alun Terminal Using the Structural Equation Modeling - Faqih Zulham Nawwaf; Hera Widyastuti (G-Tech: Jurnal Teknologi Terapan, 2026)
Transportation maintains a vital role in enabling trade and mobility, which significantly contributes to regional economic growth. Therefore, this study used Partial Least Square Structural Equation Modeling was chosen because it can analyze the causal relationship between latent variables simultaneously, while PLS-SEM was preferred because it focuses on prediction, is tolerant of normality assumptions, and is suitable for complex models with survey data. A purposive sampling technique was used and 250 data were collected through on-site survey. All manifest variables proved both valid and reliable. The variable of passenger satisfaction was shown to be low, with an R² value of 0.046, indicating that the ability of the construct or model to explain the satisfaction is very weak and almost negligible. In contrast, the loyalty variable, achieved a high R² of 0.911 which is included in the very strong category. This result shows that the model can explain 91.1% of the variance in loyalty, indicating that the model’s variables are excellent at predicting loyalty and have a high explanatory power. These results provide actionable insights for terminal administration and transport policy, highlighting the necessity to enhance service characteristics that directly improve traveler satisfaction to maintain passenger allegiance.